Impact of COVID-19 on Oral Healthcare for Oncopediatric Patients: The Setting in a Reference Hospital in Northeast Brazil - Lecidamia Cristina Leite Damascena; Paula Maria Maracajá Bezerra; Fabio Gomes dos Santos; Nyellisonn Nando Nóbrega de Lucena; Thiago Isidro Vieira; José Maria Chagas Viana Filho; Paulo Rogério Ferreti Bonan; Isabella Lima Arrais Ribeiro; Eliane Batista de Medeiros Serpa; Simone Alves de Sousa; Ana Maria Gondim Valença (Association of Support to Oral Health Research (APESB), 2022)
Objective: To describe the impact of the COVID-19 pandemic on dental care provided to pediatric cancer patients assisted in a referral hospital. Material and Methods: This is an observational, retrospective study based on secondary data extracted from worksheets of dental procedures for patients aged between 0 and 19 years assisted in the pediatric oncology sector of a hospital in João Pessoa, PB, Brazil. Dental procedures performed by the interdisciplinary team of researchers from August 2018 to February 2020 (19 months prior to the pandemic) and from April 2020 to October 2021 (19 months during the pandemic) were totaled and compared. A descriptive analysis of the data was performed. Results: There was a reduction of 80.2% in dental interventions implemented in the sector during the pandemic, with the number of procedures decreasing from 6,210 (the period before the pandemic) to 1,229 (during the pandemic). Most procedures in both periods were performed for patients assisted in beds, for whom there was a reduction of care provided for 81.2% from 5,275 to 994 procedures. Dental procedures in the outpatient clinic decreased by 74.9%, from 935 to 235. Conclusion: The COVID-19 pandemic negatively impacted dental care provided to pediatric oncology patients by restricting dental procedures to emergency demands, compromising performance prevention and health promotion actions.